Epidemiological characteristics and molecular features of carbapenem-resistant Enterobacter strains in China: a multicenter genomic study. Issue 1 (31st December 2023) - Zhu, Zhichen; Xie, Xiaofang; Yu, Hua; Jia, Wei; Shan, Bin; Huang, Bin; Qu, Fen; Niu, Siqiang; Lv, Jinnan; Gao, Qizhao; Qian, Feinan; Tian, Xiangxiang; et al.
ABSTRACT: Epidemiological characteristics and molecular features of carbapenem-resistant Enterobacter (CR- Ent ) species remain unclear in China. In this study, we performed a genomic study on 92 isolates from Enterobacter -caused infections from a multicenter study in China. Whole genome sequencing (WGS) was used to determine the genome sequence of 92 non-duplicated CR- Ent strains collected from multiple tertiary health centres. The precise species of Enterobacter strains were identified by average nucleotide identity (ANI) and in silico DNA–DNA hybridization (isDDH). Molecular features of high-risk CR- Ent sequence type (ST) lineages and carbapenemase-encoding plasmids were determined. The result revealed that the most common human-source CR- Ent species in China was E. xiangfangensis (66/92, 71.93%), and the proportion of carbapenemase-producing Enterobacter (CP- Ent ) in CR- Ent was high (72/92, 78.26%) in comparison to other global regions. Furthermore, ST171 and ST116 E. xiangfangensis were the major lineages of CP- Ent strains, and ST171 E. xiangfangensis was more likely to cause infections in older patients. Genomic analysis also highlighted the likelihood of intra-hospital/inter-hospital clonal transmission of ST171 and ST116 E. xiangfangensis . In addition, the bla NDM -harbouring IncX3-type plasmid was identified as the prevalent carbapenemase-encoding plasmid carried by CR- Ent strains, and was experimentally confirmed to be able to self-transfer with high frequency. This study detailed the genomic and clinical characteristics of CR- Ent in China in the form of multicenter for the first time. The high risk of carbapenemase-producing ST171 and ST116 E. xiangfangensis, and the bla NDM -harbouring IncX3-type plasmid were detected and emphasized.